Analisis Faktor Keterlambatan Pelaksanaan perbaikan Jalan rusak Lembar-Pelabuahan Gili Mas Lombok Barat - Anggara, Dani; Taqiudin , Muhamad; Mujahadah, Nur (Innovative: Journal Of Social Science Research, 2024)
It is hoped that the repair of the damaged road at Lemi Mas Harbor, West Lombok, Gili Mas will be able to facilitate the transportation of goods and services at Gili Mas Harbor, West Lombok. This road repair work is expected to be completed according to the implementation time stated in the contract. The research location is West Lombok Regency. In this research, a survey was conducted using a questionnaire on the workforce on the project. The delay factors considered in data collection were obtained based on literature studies. Factor analysis and ranking are carried out to see the factors that have the most significant value. The results of the analysis show that the 3 factors with the highest ratings causing delays in the repair project for the damaged Lembar-Pelabuhan Gili Mas Road, West Lombok, are unfinished contract changes (Addendums); poor implementation schedule; and slow design review drawings. Keyword: Road repairs, factor analysis, delays